Pengaruh Pelatihan dan Pengembangan Sumber Daya Manusia Terhadap Kinerja Karyawan PT Pos Indonesia (Persero) Kebonrojo Surabaya - Iqbal Maulana Ihsani; Hesty Prima Rini (Universitas Batanghari Jambi, 2023)
The research has a purpose to influence the training and development of human resources on the performance of employees at PT. Pos Indonesia (Persero) Kebonrojo Surabaya. The population of the research is the distribution division employees of PT. Pos Indonesia (Persero) Kebonrojo Surabaya with a total of 45 employees. The sampling technique used the saturated sampling method, then as a whole 45 employees of the distribution division were designated as research respondents. Data was collected by distributing questionnaires to respondents with an ordinal scale through a Likert scale on a score of 1 to 5. Furthermore, the data was processed using PLS data. The results of the study show that the training has an insignificant and positive direct effect on the performance of PT. Pos Indonesia (Persero) Kebonrojo Surabaya. Meanwhile, human resource development has a significant and positive direct influence on the performance of the employees of PT. Pos Indonesia (Persero) Kebonrojo Surabaya.